MOBILE ASSISTED LANGUAGE LEARNING AND DIGITAL STORYTELLING FOR MULTILINGUAL EDUCATION: A SYSTEMATIC REVIEW - Riska Meisyi Putri; Retno Wahyu Ningsih; Azimah Haji Ali (Yayasan Adra Karima Hubbi, 2025)
This study reviews the use of Mobile-Assisted Language Learning (MALL) and digital storytelling in multilingual educational settings. It focuses on research trends, teaching strategies, and their role in supporting inclusive and effective language learning. Using a systematic literature review, peer-reviewed studies published between 2020 and 2025 were collected from major academic databases and analyzed thematically. The findings show that combining MALL and digital storytelling improves learner engagement, motivation, intercultural awareness, and language proficiency in diverse classrooms. These approaches also support personalized learning, collaboration, and the development of critical literacy skills related to educational equity and social justice. The main contribution of this review is its integrated perspective, which views mobile learning and digital storytelling as connected pedagogical approaches in multilingual and multicultural contexts. Overall, the study highlights the potential of technology-based learning to promote learner autonomy, adaptive learning, and inclusive teaching practices. The findings also provide useful guidance for educators, policymakers, and curriculum designers in developing learning programs that respond to the needs of multilingual learners.